B‐DNA Structure and Stability: The Role of Nucleotide Composition and Order. Issue 2 (1st February 2022) - Nieuwland, Celine; Hamlin, Trevor A.; Fonseca Guerra, Célia; Barone, Giampaolo; Bickelhaupt, F. Matthias
Abstract: Invited for this month's cover are the groups of Célia Fonseca Guerra at the Vrije Universiteit Amsterdam and Leiden University, Giampaolo Barone from the Università degli Studi di Palermo, and F. Matthias Bickelhaupt at Vrije Universiteit Amsterdam and Radboud University Nijmegen. The cover picture shows the four primary interaction components (hydrogen bonding, cross‐terms, base stacking, and solvation) that determine the stability of B‐DNA duplexes. Quantum chemical analyses identify an interplay between the stabilizing hydrogen bonds between nucleotides that drive the formation of the DNA double‐strand, and the destabilizing loss of stacking interactions within individual strands combined with partial desolvation. The sequence‐dependence in the duplex stability originates mainly from the cross‐terms, which can be attractive or repulsive. Read the full text of their Research Article at 10.1002/open.202100231 . Abstract : "… through extensive analyses of the geometric and electronic structure of the single strands, we succeeded in developing a unified model to rationalize the stability of DNA duplexes …" Find out more about the story behind the front cover research at 10.1002/open.202100231 .